2016
DOI: 10.1086/688506
|View full text |Cite
|
Sign up to set email alerts
|

The Fracture of Relational Space in Depression: Predicaments in Primary Care Help Seeking

Abstract: Primary care clinicians treat the majority of cases of depression in the United States. The primary care clinic is also a site for enactment of a disease-oriented concept of depression that locates disorder within an individual body. Drawing on theories of the self and stigma, this article highlights problematics of primary care depression treatment by examining the lived experience of depression. The data come from individuals who screened positive for depressive symptoms in primary care settings and were fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 145 publications
0
6
0
Order By: Relevance
“…Research has shown that forming a coherent identity is an important part of making a successful transition to adulthood (Erikson, 1968) and for those who also face mental health symptoms during the transition, symptoms likely impact identity formation (Estroff, 1989; Skehan & Davis, 2017; Yanos, Roe, & Lysaker, 2010). For example, in a qualitative study of those seeking help for depression in primary care settings, Bromley, Kennedy, Miranda, Sherbourne, and Wells (2016) reported that participants mainly discussed their illness (depression) in terms of relationships, in particular “as a state of anxiety about the safety of one’s intimate engagement and relational value” (p., 15). They found that identification with depression as a disease was reported mainly by those who reported a need for treatment (e.g., medication).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Research has shown that forming a coherent identity is an important part of making a successful transition to adulthood (Erikson, 1968) and for those who also face mental health symptoms during the transition, symptoms likely impact identity formation (Estroff, 1989; Skehan & Davis, 2017; Yanos, Roe, & Lysaker, 2010). For example, in a qualitative study of those seeking help for depression in primary care settings, Bromley, Kennedy, Miranda, Sherbourne, and Wells (2016) reported that participants mainly discussed their illness (depression) in terms of relationships, in particular “as a state of anxiety about the safety of one’s intimate engagement and relational value” (p., 15). They found that identification with depression as a disease was reported mainly by those who reported a need for treatment (e.g., medication).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Poor mental health in single mothers is associated with financial insecurity and increased frequency of daily stressors [5]. Other data show that access to support networks is essential in empowering people cope with every-day problems and manage challenges [6, 7]. Studies has shown that higher levels of mastery and social support were found to be associated with less depressive symptoms [8], and that single mothers without additional personal support for their child, younger, as well as poor single mothers showed higher values of psychological distress [9].…”
Section: Introductionmentioning
confidence: 99%
“…We qualitatively analyzed program representative interviews to determine how agencies meet their clients' multiple needs. As in previous work, 31 we created interview summaries with verbatim quotes from audio recordings and entered them into RedCap -a secure, web-based, data capture and management tool. We used both deductive and inductive approaches to data coding.…”
Section: Discussionmentioning
confidence: 99%